Utilization of E-Commerce and Digital Marketing in Increasing Customer Purchasing Decisions at CV. CS Lestari Jaya Kisaran - Michael; Sri Rezeki (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
At CV.  CS  Lestari  Jaya,  a  decline  in  sales  is  evident  due  to  a  continuous  decrease  in  customer  purchases.  This  drop  in  customer  purchasing  decisions  may  be  linked  to  the  company's limited  use  of  e-commerce  and  digital  marketing  strategies.  The  aim  of  this  study  is  to  assess  how the  use  of  e-commerce  and  digital  marketing  can  influence  customer  purchasing  decisions  at CV.  CS  Lestari  Jaya  Kisaran.  This  research  is  quantitative  in  nature,  with  a  population  of  149 customers  who  made  purchases  at  CV.  CS  Lestari  Jaya  Kisaran  in  2023.  The  sample  size  was determined  using  the  Slovin  formula  with  a  5%  standard  error,  resulting  in  109  samples.  The findings  indicate  that  both  e-commerce  and  digital  marketing  have  a  significant  impact  on customer  purchasing  decisions,  both  individually  and  together.  To  enhance  customer purchasing  decisions,  it  is  crucial  for  CV.  CS  Lestari  Jaya  Kisaran  to  effectively  leverage  e-commerce platforms  and  digital  marketing  strategies.  Furthermore,  running  targeted  paid  advertising campaigns  on  these  platforms  can  help  reach  specific  audiences  based  on  demographics  and interests,  increasing  the  likelihood  of  conversions